First- and second-sphere contributions to Fe(II) site activation by cosubstrate binding in nonheme Fe enzymes - Light, Kenneth M. (2014)
Nonheme Fe(II) enzymes exhibit a general mechanistic strategy where binding all cosubstrates opens a coordination site on the Fe(II) for O(2) activation. This study shows that strong-donor ligands, steric interactions with the substrate and second-sphere H-bonding to the facial triad carboxylate allow for five-coordinate site formation in this enzyme superfamily.